2005
DOI: 10.1038/sj.leu.2404030
|View full text |Cite
|
Sign up to set email alerts
|

The G(-248)A polymorphism in the promoter region of the Bax gene does not correlate with prognostic markers or overall survival in chronic lymphocytic leukemia

Abstract: The G(-248)A polymorphism in the promoter region of the Bax gene was recently associated with low Bax expression, more advanced stage, treatment resistance and short overall survival in B-cell chronic lymphocytic leukemia (CLL), the latter particularly in treated patients. To investigate this further, we analyzed 463 CLL patients regarding the presence or absence of the G(-248)A polymorphism and correlated with overall survival, treatment status and known prognostic factors, for example, Binet stage, V H mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 23 publications
4
32
1
1
Order By: Relevance
“…The presence of certain SNPs within the BAX [25], P2X7 [26], GNAS1 [27] and BCL2 [28] genes have been associated to disease progression and inferior survival for the patients. However, none of these potential SNPs have been confirmed in subsequent investigations by other groups [19,[29][30][31][32]. Thus, it is important that any potential SNP should be verified by large independent cohorts and independent research centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of certain SNPs within the BAX [25], P2X7 [26], GNAS1 [27] and BCL2 [28] genes have been associated to disease progression and inferior survival for the patients. However, none of these potential SNPs have been confirmed in subsequent investigations by other groups [19,[29][30][31][32]. Thus, it is important that any potential SNP should be verified by large independent cohorts and independent research centers.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from frozen tumor cells as previously described [19]. DNA was whole-genome amplified according to the manufacturer's protocol (GenomiPhi DNA Amplification, GE Healthcare, Uppsala, Sweden).…”
Section: Analysis Of the Mdm2 Snp309 Polymorphismmentioning
confidence: 99%
“…20 Skogsberg et al, however, concluded that the Bax-248 polymorphism had no role as a marker of survival and prognosis in CLL. 21 The exact cause of MPNs is unknown. However, molecular-genetic studies suggest that the majority of this type of neoplasm may be the result of acquired clonal genetic events.…”
Section: Discussionmentioning
confidence: 99%
“…11 DNA was whole-genome amplified according to the manufacturer's protocol (GenomiPhi DNA Amplification, GE Healthcare, Uppsala, Sweden). For genotyping, information on PCR and minisequencing primers was collected from the SNP assay database (http://las.perkinelmer.com/content/forms/SNPDatabase/ welcome.asp).…”
Section: Analysis Of the Bcl-2 (à938c4a) Promoter Polymorphismmentioning
confidence: 99%
“…9 Recently, single-nucleotide polymorphisms (SNPs) within certain genes (BAX, P2X7, GNAS1 and MCL-1) have also been associated with disease progression and clinical outcome, although none of these studies has been confirmed in subsequent studies from other centers. [10][11][12][13][14][15][16][17] Bcl-2 belongs to a growing family of apoptosis-regulatory gene products, comprising both proapoptotic (Bax, Bak, Bcl-X S , Bad, Bid, Bik and Hrk) and antiapoptotic (Bcl-2, Bcl-X L , Bcl-W, Brag-1, Mcl-1 and Bfl-1/A1) members. 18,19 CLL cells have been shown to display dysregulated apoptosis with high expression of the Bcl-2 protein in most cases.…”
Section: Introductionmentioning
confidence: 99%